Faktor-Faktor Yang Berhubungan Dengan Dermatitis Kontak Pada Nelayan Di Wilayah Kenagarian Koto Kaciak Kabupaten Agam - Intan kamala aisyiah; Sri Mindayani; Afifah Ramadhani (Jurnal Vokasi Keperawatan (JVK), 2023)
Contact dermatitis is an occupational disease that can reduce the health level of workers and will ultimately affect overall work productivity. The results of observations at Koto Kaciak Region, there are fishermen who feel itchy (40%), have reddish skin (20%), yellowish nails (20%), and dry skin (20%). The aim of this study was to look at the factors associated with contact dermatitis in fishermen. This type of research is quantitative research with an analytic survey using a cross-sectional approach. Total population of 65 fishermen and using a total sampling technique. The results of the univariate analysis showed that 73.8% of respondents had contact dermatitis, 63.1% of respondents were at risk of developing contact dermatitis, 53.8% of respondents had low knowledge, 60% of respondents had poor personal hygiene and 87.7% of respondents had a history of skin disease. The results of the bivariate analysis showed that there was no significant relationship between age (p-value = 0.650) and knowledge (p-value = 0.446) of contact dermatitis, but there was a relationship between personal hygiene (p-value = 0.033) and history of skin disease (p-value = 0.048) with contact dermatitis in fishermen. It is hoped that fishermen who return to work immediately change their clothes and routinely check themselves at the health service, and continue to attend counseling about contact dermatitis. For fishermen who are at risk of experiencing contact dermatitis, it can reduce physical activity.